22-year trends in dysglycemia and body mass index: A population-based cohort study in Savitaipale, Finland. Issue 6 (December 2021) - Saramies, Jouko; Koiranen, Markku; Auvinen, Juha; Uusitalo, Hannu; Hussi, Esko; Cederberg, Henna; Keinänen-Kiukaanniemi, Sirkka; Tuomilehto, Jaakko
Highlights: A description of the study design and population of the Savitaipale Study in Finland. A 22-year prospective population-based and cohort study. The main aim was to assess changes in cardiometabolic factors in middle-aged people. People with normal glucose metabolism rapidly converted to dysglycaemia and diabetes. BMI remained unchanged, systolic blood pressure increased and lipid values improved. Abstract: Aims: We describe a 22-year prospective observational population-based study that determined the prevalence and incidence of type 2 diabetes (T2D) and intermediate hyperglycaemia (IH), obesity, hypertension, and disorders of lipid metabolism in a middle-age population in the Finnish municipality of Savitaipale. Methods: 1151 people participated in the baseline survey in 1996–1999, following two follow-up examinations, in 2007–2008 and 2018−2019. Follow-up studies comprised clinical measurements, 2-h oral glucose tolerance test and other biochemistry, questionnaires, and registry data. Results: The prevalence of T2D quadrupled to 27% and the proportion of normoglycemic people decreased from 73% to 44% while IH increased only slightly during the 22-year follow-up. A large proportion of people who died between the surveys were diabetic. The mean body mass index (BMI) did not, whereas mean waist circumference increased significantly, by 5−6 cm (P = 0.001) during the 22 years. Systolic blood pressure increased by 13−15 mmHg from baseline (P = 0.0001) but diastolic blood pressure did not. The mean plasma levels of total and LDL-cholesterol decreased 10.8% and 8.9% in women (P = 0.001), 21.5% and 22.2% in men (P = 0.001), respectively, while HDL-cholesterol and triglycerides remained stable. The proportion of those achieving targets in the treatment of dyslipidaemia increased significantly (P < 0.001). Conclusions: In this 22-year prospective follow-up study of in middle-aged Europeans with high participation rates, the progression of dysglycaemia to overt diabetes with aging was rapid, even without a significant change in BMI.